A Dutch translation and validation of the Body Appreciation Scale-2: An investigation with female university students in the Netherlands. (December 2016) - Alleva, Jessica M.; Martijn, Carolien; Veldhuis, Jolanda; Tylka, Tracy L.
Highlights: The Dutch Body Appreciation Scale-2 (BAS-2) has a one-dimensional factor structure. Dutch BAS-2 scores demonstrated good internal consistency. Dutch BAS-2 scores evidenced construct (convergent, incremental) validity. There was an inverse relationship between Dutch BAS-2 scores and body mass index. Abstract: This paper describes a Dutch translation and validation of the Body Appreciation Scale-2 (BAS-2;Tylka & Wood-Barcalow, 2015a ), an instrument for assessing key components of positive body image. Dutch-speaking female university students ( N  = 310, M age  = 21.31, SD  = 3.04) completed the Dutch BAS-2. To assess its construct validity, participants also completed measures of appearance satisfaction, functionality satisfaction, self-objectification, self-esteem, and optimistic life orientation. Exploratory factor analysis revealed a one-dimensional factor structure of the Dutch BAS-2, substantiating the BAS-2 factor structure found in samples of U.S., Chinese, and Iranian university students and community adults. Dutch BAS-2 scores also demonstrated good internal consistency ( α  = .90), convergent validity, and incremental validity. In addition, lower body mass indices were associated with higher Dutch BAS-2 scores. The present findings support the cross-cultural equivalence of the BAS-2 and thus its promise in enabling research on positive body image in diverse cultural contexts.